Relationship Length of Time Patient Waiting In Poly Interne With Patient Satisfaction In Dr. Achmad Mochtar Bukittinggi Year 2017 - Tafdiel Tafdiel; Rinawati Kasrin (Jurnal Kesehatan - STIKes Prima Nusantara, 2018)
Waiting time is the time that patients use to get health services starting from the place of registration until entering the doctor examination room. Patient waiting time is one component that causes patient dissatisfaction, which if patient waiting time is not in accordance with the standard that has been set that is for wait time is â‰¤ 60 minutes it will affect the patient satisfaction. The fact shows still found the patient complained waiting time in poli interne. This study aims to determine the relationship between patient waiting time in poly interne with patient satisfaction in Bukittinggi Hospital in 2017. Type of research used is quantitative with a cross-sectional approach. The population in this study amounted to 420 patients with the number of samples obtained as much as 81 using the technique of non-probability sampling that is accidental sampling. Data were analyzed using the chi-square test. The result of the analysis is more than partially (72.8%) nonstandard waiting time, (27.2%) standard waiting time. Bivariate analysis was found (66.1%) waiting time was not according to the standard of an unsatisfied patient, and (13.6%) waiting time according to standard and patient was not satisfied. Statistical test results obtained p-value 0.0001 (p <0.05), OR = 12.350. The conclusion of this study is there is a significant relationship between patient waiting time and patient satisfaction in RSUD Dr. Achmad Muchtar Bukittinggi in 2017. It is expected that employees and health workers to maintain and improve the performance and service to patients in accordance with predetermined standards, so patients will be satisfied if their expectations are in accordance with the desired.Â